2016
DOI: 10.3109/03014460.2015.1126353
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of genetic variants of oxidative stress metabolism genes: Paraoxonase 1 (PON1) and Glutathione S-transferase (GSTM1/GSTT1) in a population from Southeastern Mexico

Abstract: The results showed that the frequencies of polymorphisms of PON1, GSTM1 and GSTT1 in the Yucatán population differ to those observed in other ethnic groups and provide useful data for epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
3
1
Order By: Relevance
“…We observed differences in the activities of PON1 according to Q192R genotype. The genotype distribution found in the current study was not different from that found in other Mexican populations [10,[53][54][55]. Few studies have reported PON1 specific activities.…”
Section: Discussioncontrasting
confidence: 69%
“…We observed differences in the activities of PON1 according to Q192R genotype. The genotype distribution found in the current study was not different from that found in other Mexican populations [10,[53][54][55]. Few studies have reported PON1 specific activities.…”
Section: Discussioncontrasting
confidence: 69%
“…Interestingly, the worldwide frequencies of the GSTM1 and GSTT1 null genotypes are extremely variable, with ranges from 0.11 to 0.67 and from 0.10 to 0.51, respectively (Buchard et al, 2007; Kumar et al, 2012). In the Mexican‐Mestizo population, the distribution of the GSTM1 and GSTT1 null genotypes varies from north to south, between 0.48 and 0.31 and between 0.13 and 0.09, respectively (García‐González et al, 2016; Palma‐Cano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found no significant difference in the frequencies of the GSTT1 and GSTM1 null genotypes among Mexican-Mestizo and Tarahumara individuals from the northwestern region of the country. In addition, we observed a high variability in the frequency of the null genotypes for GSTT1 and GSTM1 among the different geographic regions of the country, ranging from 0.03 to 0.17 for GSTT1 and from 0.22 to 0.48 for GSMT1 ( Pérez-Morales et al , 2008 , 2011 ; Sánchez-Guerra et al , 2012 ; Gutiérrez-Amavizca et al , 2013 ; Sandoval-Carrillo et al , 2014 ; García-González et al. , 2015 ; Jaramillo-Rangel et al , 2015 ).…”
Section: Discussionmentioning
confidence: 89%
“…Although studies about the distribution of GSTM1 and GSTT1 null genotypes in a Mexican-Mestizo population have been performed previously ( Pérez-Morales et al , 2008 ; Pérez-Morales et al , 2011 ; Sánchez-Guerra et al. , 2012 ; Gutiérrez-Amavizca et al , 2013 ; Sandoval-Carrillo et al , 2014 ; García-González et al , 2015 ; Jaramillo-Rangel et al , 2015 ) no reports of the prevalence of these variants in Mexican Amerindian individuals are available. Thus, the aim of this study was to determine and compare the frequencies of GSTM1 and GSTT1 null genotypes in Mexican-mestizo and Amerindian individuals (Tarahumara) from the Northwestern part of the country (State of Chihuahua) with those previously found in other regions of Mexico and around the world.…”
Section: Introductionmentioning
confidence: 99%